2019
DOI: 10.1002/hep.30250
|View full text |Cite
|
Sign up to set email alerts
|

From Hepatocyte to Cholangiocyte: The Remarkable Potential of Transdifferentiation to Treat Cholestatic Diseases

Abstract: Transdifferentiation involves the conversion of one mature cell type into a distinctly different, specialized cell type. Schaub et al. have recently discovered the TGFβ-mediated mechanism of hepatocyte transdifferentiation into cholangiocytes in a mouse model of Alagille syndrome. Prior studies primarily focused on murine models of injury and manipulation of the proliferative capabilities of the original cholangiocytes. The novelty of the current study lies in the generation of functional intrahepatic bile duc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…(8,28) Typically in rodent models, mature hepatocytes transdifferentiate into either fully functional cholangiocytes or a cholangiocyte-like phenotype when there is extensive injury and resident cholangiocytes lose functionality and are incapable of adequately proliferating to compensate for the injury. (6,(29)(30)(31) Similar results have also been observed in humans. Hepatocytes from both pediatric and adult cholangiopathy patients have been reported to express the ductal/oval cell marker OV-6, (32,33) cholangiocytespecific cytokeratins, (34)(35)(36) and biliary transcription factors.…”
Section: Discussionsupporting
confidence: 85%
“…(8,28) Typically in rodent models, mature hepatocytes transdifferentiate into either fully functional cholangiocytes or a cholangiocyte-like phenotype when there is extensive injury and resident cholangiocytes lose functionality and are incapable of adequately proliferating to compensate for the injury. (6,(29)(30)(31) Similar results have also been observed in humans. Hepatocytes from both pediatric and adult cholangiopathy patients have been reported to express the ductal/oval cell marker OV-6, (32,33) cholangiocytespecific cytokeratins, (34)(35)(36) and biliary transcription factors.…”
Section: Discussionsupporting
confidence: 85%
“…179 Finally, trans-differentiation (cellular reprogramming) of hepatocytes into mature cholangiocytes has been demonstrated after extensive injury and loss of biliary cells, for example, after hepatectomy, bile duct ligation, or an acute toxic insult, when proliferation of resident cholangiocytes or progenitor cells cannot adequately compensate for this loss. [180][181][182][183] More importantly, this transdifferentiation is able to build permanent ductules, which successfully contribute to bile drainage and remain after the initial liver injury is reversed 184 ; this contrast with metaplasia of injured hepatocytes that form proliferative biliary pseudoductules as part of the so-called "ductular reaction," [185][186][187][188][189] which is reversible in nature 186,187 and does not contribute to bile drainage. 189 Several reprogramming factors have been implicated in hepatocyte-derived biliary transdifferentiation, including cytokines (e.g., TNF-α 190 and transforming growth factor [TGF]-β 184 ), growth factors (e.g., hepatocyte growth factor 191 and epidermal growth factor 191,192 ), some downstream mediators of the protein-tyrosine phosphorylation pathways stimulated by them (e.g., PI3K 191,192 and ERK 192 ), the Notch 180,193,194 and Hippo 195 developmental pathways, and transcription factors whose expression is modulated by these signaling pathways (e.g., Sox9, 196 Oct4 197 ).…”
Section: Stimulators Of Cholangiocyte Proliferationmentioning
confidence: 99%
“…Because bile stasis is a hallmark of cholangiopathies, reestablishing bile flow may help reduce injury or slow the progression of cholestatic diseases. To that end, the generation of de novo healthy ducts through the induction of hepatocyte reprogramming may be of significance in promoting repair in diseases such as PSC 136 . Indeed, a recent publication has demonstrated that transplanted mouse hepatocytes can build a biliary system in vivo by permanently transdifferentiating into mature cholangiocytes that form functional bile ducts 103 …”
Section: β-Catenin Modulation For Therapiesmentioning
confidence: 99%
“…To that end, the generation of de novo healthy ducts through the induction of hepatocyte reprogramming may be of significance in promoting repair in diseases such as PSC. [136] Indeed, a recent publication has demonstrated that transplanted mouse hepatocytes can build a biliary system in vivo by permanently transdifferentiating into mature cholangiocytes that form functional bile ducts. [103] Because of its role in promoting the expression of biliary markers in hepatocytes, activation of β-catenin by clinically feasible means may be highly significant.…”
Section: β-Catenin Modulation For Therapiesmentioning
confidence: 99%